A multiwavelength study of distant blazar PKS 0537-286 - Sahakyan, N.; Israyelyan, D.; Harutyunyan, G. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We report the results of broadband observations of distant blazar PKS 0537-286 ( z=3.1 ) using data spanning more than ten years from the Fermi Large Area Telescope together with Swift UVOT/XRT archival data taken between 2005 and 2017. Представлены результаты многоволновых наблюдений далекого блазара PKS 0537-286 ( z=3.1). Использованы данные, накопленные в течение более чем десяти лет телескопом Fermi-LAT вместе с архивными данными Swift UVOT/XRT, за период 2005-2017гг.
Keywords: Astrophysics